Endothelial Cell Hypertrophy and Microvascular Proliferation in Meningiomas Are Correlated with Higher Histological Grade and Shorter Progression-Free Survival. Issue 12 (December 2016) - Ling, Catherine; Pouget, Celso; Rech, Fabien; Pflaum, Robin; Treffel, Mathilde; Bielle, Franck; Mokhtari, Karima; Casse, Jean-Matthieu; Vignaud, Jean-Michel; Kalamarides, Michel; Peyre, Matthieu; Gauchotte, Guillaume
Abstract : Microvascular proliferation (MVP) is a hallmark of glioblastoma. Endothelial cell hypertrophy (ECH), also known as endothelial hyperplasia, is correlated with a shorter survival of patients with gliomas. However, the prognostic value of these 2 morphological features has not been studied in meningiomas. The aim of this study was to evaluate the prognostic value of angiogenesis in meningiomas, most notably ECH, MVP, and microvascular density, which were evaluated using immunohistochemistry with antibodies against CD34 and CD105 (a marker of neovascularization) in a series of 139 meningiomas. ECH, MVP, and CD105 immunoreactivity were significantly correlated with higher histological grades (p < 0.0001, p = 0.0004, and p = 0.0003, respectively). ECH and MVP but not CD105 immunoreactivities were significantly correlated with a shorter progression-free survival time (PFS) (p = 0.017, p = 0.021, and p = 0.137, respectively). In Cox multivariate analysis, ECH was an independent predictor of shorter PFS (p = 0.028). Therefore, ECH and MVP are markers of shorter PFS in meningiomas and are significantly correlated with grade. These findings give insight into the use of anti-angiogenic therapies. Further studies are needed to determine whether these markers could allow us to identify patients who could benefit from anti-angiogenic therapies.